A visual analytics framework for strategic airlift decision making. (April 2013) - Soban, Danielle S; Salmon, John; Fahringer, Phil
The foundational concept of Network Enabled Capability relies on effective, timely information sharing. This information is used in analysis, trade and scenario studies, and ultimately decision making. In this paper, the concept of visual analytics is explored as an enabler to facilitate rapid, defensible and superior decision making. By coupling analytical reasoning with the exceptional human capability to rapidly internalize and understand visual data, visual analytics allows individual and collaborative decision making to occur in the face of vast and disparate data, time pressures and uncertainty. An example visual analytics framework is presented in the form of a decision-making environment centered on the Lockheed C-5A and C-5M aircraft. This environment allows rapid trade studies to be conducted on design, logistics and capability within the aircraft's operational roles. Through this example, the use of a visual analytics decision-making environment within a military environment is demonstrated.